Profil Kimia dan Hedonik Snack Bar dari Tepung Biji Kecipir dengan Pengikat Tapioka - Aminullah, Aminullah; Kusumah, Fajrin Safta; Kusumaningrum, Intan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPA, 2025)
Winged bean flour which contains high protein, could be processed into snack bar products by adding starch binders. The objective of this research was to study the effect of winged bean flour and sesame seeds mixture with tapioca binders and their interaction on the caloric and protein of snack bars and the hedonic character. This research used a two-factor completely randomized design with three treatment levels: a mixture of winged bean flour: sesame seeds at 90:10, 80:20, and 70:30, and the addition of tapioca at 15%, 20%, and 25% with two replications. Data were analyzed using ANOVA and Duncan's post hoc test (?=0,05), while hedonic data were analyzed using Kruskal Wallis test and Mann Whitney post hoc test. The results showed that the higher the sesame seed addition, the higher the protein and caloric values of the snack bar. In addition, the higher the tapioca concentration led to the higher the caloric value; however, tapioca addition tends to have no significant effect on the protein content of snack bars. The interaction of winged bean flour and sesame seeds with tapioca affected the protein content but not the calorific value. Based on the hedonic test, the panelists' preference for color, aroma, taste, texture, and overall parameters tended to increase with the number of sesame seeds in the snack bar. The snack bar treatment with 70% winged bean flour, 30% sesame seeds, and 15% tapioca starch got the highest preference rating of all tested parameters. The results of chemical analysis on the snack bar with the highest level of preference showed water content of 16.97%, ash content of 1.18%, a fat content of 11.37%, a carbohydrate content of 50.52%, protein content of 19.97%, dietary fiber of 18.28%, the calorific value of 115.28 kcal/30 g serving, and hardness of 2051.83 gF.